Effect of increasing salinity on the perfromance of genetically profiled tilapia - Gelletu, Emebet Chaka (Miag-ao, Iloilo College of Fisheries and Ocean Sciences, U. P. in the Visayas, 2003)
The study was conducted to assess the effect of increasing salinity levels on the performance of nine different tilapia families and a reference strain (Oreochromismossmabicus) for 120 days using 15-20 ppt for 60 days and 20-25 ppt for the next 60 days. Performance was measured in terms of growth and survival. Survival was monitored for the 120 day culture period. Growth was also measured but the study involved multiple sex crops, this was further assessed using the nucleic acid content of the fish strains used. Measurements were taken every 15 days while the nucleic acid test was made on the initial and final samples only. Results on survival showed that Family 8 (O. niloticus (IDRC) x O. spilurus) is the best strain with 98% survival rate during the whole culture period. This may due to the O. spilurus factor because the strain is known to be a saline tolerant one. The low survival of O. mossambicus (control animal) occured at the 60th (45.67%) day of sampling when iced water was used. Thereafter, this practice was not repeated because of the high levels of mortality indicating that all tilapia strains used may not be able to adopt to sudden change in temperature specifically the increase from low to high temperature range since death occurred after sampling has been completed. On the other hand, fish muscle was used for the analysis of RNA and DNA content and the RNA/DNA ratio was used for the determination of the growth of the fish. The growth potential using RNA/DNA ratio showed a significant difference between the various strains. However, Family 7 which has a pedigree composition of O. niloticus (IDRC) x O. niloticus (IDRC) for sire and O. mossambicus x O. niloticus (IDRC) for dam showed best results. The high growth rate potential of this species may be attributed to the O. niloticus pedigree since this tilapia species is usually a desired culture species because of its known fast growth rate. The growth data collected during the experiment were affected by the fact the strains used included both male and female individuals. However, inspite of this no significant difference was observed among all the families used. Based on the results of the study, the pedigree composition of both Families 7 and 8 are the desirable species for culture.
Thesis (M. S. Fisheries-Aquaculture) - U. P. in the Visayas, October 2003.
Keywords: Salinity; Tilapia